The larvae of the Aegean endemic caddisflies Hydropsyche debirasi Malicky 1974 and Hydropsyche kleobis Malicky 2001 (Trichoptera: Hydropsychidae) with notes on their ecology and zoogeography - Karaouzas, Ioannis (Zootaxa, 2013)
The larvae of Hydropsyche debirasi Malicky 1974 and Hydropsyche kleobis Malicky 2001, endemics of the Aegean Is-lands, Greece, are described for the first time. The diagnostic features of the species are described and illustrated and some information regarding their ecology and zoogeography are included.